2017
DOI: 10.1038/s41598-017-00067-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel protein acetyltransferase, Rv2170, modulates carbon and energy metabolism in Mycobacterium tuberculosis

Abstract: Recent data indicate that the metabolism of Mycobacterium tuberculosis (Mtb) inside its host cell is heavily dependent on cholesterol and fatty acids. Mtb exhibits a unique capacity to co-metabolize different carbon sources and the products from these substrates are compartmentalized metabolically. Isocitrate lies at one of the key nodes of carbon metabolism and can feed into either the glyoxylate shunt (via isocitrate lyase) or the TCA cycle (via isocitrate dehydrogenase (ICDH) activity) and we sought to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…While N α -acetylation in eukaryotes has been well studied, little is known about it in bacteria, including mycobacteria. Over 100 proteins in Mtb have been found to be N α -acetylated, including EsxA (32), and protein acetylation has been correlated to pathogenesis (33,34). Currently, three N α -acetyltransferases in E. coli, RimI, RimL and RimJ, have been identified to acetylate ribosomal proteins S18, L12 and S5, respectively (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While N α -acetylation in eukaryotes has been well studied, little is known about it in bacteria, including mycobacteria. Over 100 proteins in Mtb have been found to be N α -acetylated, including EsxA (32), and protein acetylation has been correlated to pathogenesis (33,34). Currently, three N α -acetyltransferases in E. coli, RimI, RimL and RimJ, have been identified to acetylate ribosomal proteins S18, L12 and S5, respectively (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Over 100 proteins in Mtb have been found to be N α -acetylated, including EsxA (32), and protein acetylation has been correlated to pathogenesis (33,34). Currently, three N α -acetyltransferases in E. coli, RimI, RimL and RimJ, have been identified to acetylate ribosomal proteins S18, L12 and S5, respectively (34)(35)(36). A biochemical study has found RimI in Mtb has a relaxed substrate specificity, but little is known about the physiological substrates of the enzyme (37), which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Rv2170 is a protein acetyltransferase with the ability to acetylate, succinylate, and propionylate isocitrate dehydrogenase (Icd1/Rv3339c). As with the modification of other metabolic enzymes, acetylation of Icd1 reduces isocitrate dehydrogenase activity and shifts fatty acid metabolism toward the glyoxylate cycle and reduces flux through the TCA cycle [28]. Acetylation of isocitrate lyase (Icl) has varying effects on enzymatic activity and protein stability depending on the site of the modification [29].…”
Section: Post-translational Modifications Regulate Metabolic Enzyme Amentioning
confidence: 99%
“…A succinyltransferase has not been definitively identified. Mt Pat and Rv2170 [28] may catalyze succinylation in addition to acetylation and/or propionylation. Rv0802c, a GCN5-related N-acetyltransferase (GNAT) family member, co-crystallizes with succinyl-CoA suggesting that Rv0802c catalyzes succinylation of lysines [35].…”
Section: Post-translational Modifications Regulate Metabolic Enzyme Amentioning
confidence: 99%
“…Previously, the M. tuberculosis Rv2170 KAT protein was found to acetylate key lysines on isocitrate dehydrogenase (ICDH), which results in a reduction of ICDH activity (87). Other identified type IV KATs include Porphyromonas gingivalis Pat (88), Bacillus subtilis AcuA (89), Saccharopolyspora erythraea SacAcuA (90), Rhodopseudomonas palustris RpKatA (71), Sulfolobus solfataricus Pat (91, 92), and S.…”
Section: Introductionmentioning
confidence: 99%